Intelectuales y estrategias de legitimación del leguiismo en torno a la reincorporación de Tacna al Perú (1929) - Vargas Murillo, Alfonso Renato (2023)
This article explores the construction of the memory of captivity and the reincorporation of Tacna into Peru after the War of the Pacific. It examines the reactions generated by the 1929 Treaty of Lima and the role of the newspaper La Patria in promoting a positive view of this process. The discourse of memory highlights heroism, resistance, and regional identity, projecting a future of progress and collaboration between Peru and Chile. However, it considers the political influence and the need to legitimize the government of Leguía in the face of economic crisis and unemployment in the region. The article analyzes how this discourse intertwines with other official discourses and the political and social tensions of the time, and examines the role of key intellectuals in the legitimization of the government. The aim is to understand the construction and implications of this memory in the historical and political context.